The positive effects of resource-oriented training on students’ perception and use of social support - Schmiedl, Annika; Kauffeld, Simone (Frontiers in Education, 2023)
Introduction University students are confronted with various demands that can lead to mental health problems, including depression, anxiety, or stress. One significant resource that has been shown to prevent or buffer mental health problems is social support. However, interventions enhancing students’ perception and use of social support are rare in higher education research. This study evaluates the effects of resource-oriented training following the Zurich Resource Model on students’ perception and use of social resources. Method Participants included 247 students from a German university who enrolled in the training program and were divided into intervention and waiting control groups. Results Compared to the control group, the intervention group reported higher perceived social support, increased quality of received social support, and increased seeking social support as a coping strategy four weeks after the intervention. The study results further reveal changes in support network composition in both groups over time and offer insights into the characterization of energy givers and energy eaters within one’s support network. Discussion The discussion concludes with implications, limitations, and directions for future research.